Dinamika Pelayanan Imam dan Kehidupan Keluarga di Masa Pandemi COVID-19 - Gallileo, Gabriel; Ediwanto, Aleksius (Felicitas, 2021)
The struggles of faith experienced by the people during this pandemic also have an influence on the growth of their faith. Most of the people have a big enough desire to be able to return to the offline Eucharistic celebration, because they also need a refresher of faith. In the midst of all the limitations that exist, the fighting power and enthusiasm of the people in developing their faith seems to be burning. The dynamics experienced by Christian families during this Pandemic are also very limited. They also face various difficulties and challenges, even to a greater extent, especially related to the economy. This remains a challenge that must be faced with faith. All of this is proven by his faithfulness in personal and collective prayers in the family, and is a real source of strength in facing their day to day both in their own families and in their activities and work. really live the celebration of the Eucharist and the prayers that they follow. In other words, the struggle of the people in their loyalty to foster faith is maintained in the midst of all existing limitations.